Ini Politik Identitas dan Multikulturalisme Pada Film Ngeri-Ngeri Sedap - stefani, Stefani; Kustiawan; Aurellia Tiffani Putri; Nabilla Amalia; Kinanti Anjani Putri (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This scientific paper aims to see how Batak identity politics and multiculturalism in Ngeri-Ngeri Sedap film. The research method uses a descriptive qualitative approach with a case study in the film Ngeri-Ngeri Sedap. This research explores identity politics and multiculturalism in the film ‘Ngeri-Ngeri Sedap’. The main conflict in the film relates to the cultural differences between the Batak tribe and other tribes, especially when Domu, the main character, wants to marry a woman from the Sundanese tribe. Identity politics are highly visible in Mr Domu's efforts to maintain Batak customs, including male dominance in the family and the prohibition of marrying outside the Batak tribe. This conflict reflects the strong influence of customs and traditional values in Batak society. On the other hand, multiculturalism is revealed through the interaction of Sahat, a Batak, with the Javanese community in Yogyakarta, where he is respected despite coming from a different cultural background. The film illustrates the dynamics between maintaining tradition and adapting to change, and highlights how traditional values can clash with multicultural realities in modern society. In conclusion, the film asserts that identity politics and multiculturalism play an important role in shaping the narrative and conflicts between characters, reflecting the cultural complexity that exists in Indonesian society.